Physicochemical characterisation and substrate specificity of purified ß-1,6-glucanase from Trichoderma longibrachiatum - Mustafa, Muskhazli; Abd. Aziz, Nor Azwady; Kaimi, Anida; Noor, Nurul Shafiza; Ahmad Bedawi, Salifah Hasanah; Ithnin, Nalisha (Universiti Putra Malaysia Press, 2009)
The ß-1,6-glucanases are ubiquitous enzymes which appear to be implicated in the morphogenesis and have the ability to become virulence factor in plant-fungal symbiotic interaction. To our knowledge, no report on ß-1,6-glucanases purification from Trichoderma longibrachiatum has been made, although it has been proven to have a significant effect as a biocontrol agent for several diseases. Therefore, the aim of this study was to purify ß-1,6- glucanase from T. longibrachiatum T28, with an assessment on the physicochemical properties and substrate specificity. ß-1,3-glucanase enzyme, from the culture filtrate of T. longibrachiatum T28, was successively purified through precipitation with 80% acetone, followed by anionexchange chromatography on Neobar AQ and chromatofocusing on a Mono P HR 5/20 column. (One ß-1,6-glucanase) band at 42kDa in size was purified, as shown by the SDS-PAGE. The physicochemical evaluation showed an optimum pH of 5 and optimum temperature of 50°C for enzyme activity with an ability to maintain 100% enzyme stability. Enzyme activity was slightly reduced by 10-20% in the presence of 20 mM of Zn2+, Ca2+, Co2+, Mg2+, Cu2+, Mn2+ and Fe2+. The highest ß-1,6-glucanase hydrolysis activity was obtained on pustulan due to the similarity of ß-glucosidic bonds followed by laminarin, glucan and cellulose. Therefore, it can be concluded that the characterization of ß-1,6- lucanase secreted by T. longibrachiatum in term of molecular weight, responsed to selected physicochemical factors and the substrate specificity are approximately identical to other Trichoderma sp.